Optimalisasi Pemanfaatan Dana Desa dalam Pembangunan Infrastruktur di Desa La’bo’ Kecamatan Sanggalangi Kabupaten Toraja Utara - Biringan, Julien; Supit, Arie (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
The research used an exploratory descriptive-qualitative approach, collecting data through interviews and documentation from La'bo' Village government agencies. Geographical characteristics influence the village's development, with agricultural land covering 39.6% of its area. Infrastructure development, including roads and highways, is crucial for community mobility. Village Funds (APBN) contributed 91.5% of total costs during 2019–2023. Road maintenance is the most expensive type, followed by concrete rebate and irrigation construction. Despite a decrease in funding due to the COVID-19 pandemic, economic recovery in 2021, 2022, and 2023 is expected to resume infrastructure development. The choice of materials and weather conditions also impact the construction and maintenance processes.